PVA/ MLG/ MWCNT hybrid composites for X band EMI shielding – Study of mechanical, electrical, thermal and tribological properties. (June 2020) - Joseph, Jomy; Sharma, Abhishek; Sahoo, Baidehish; Paul, Jinu; Sidpara, Ajay M.
Abstract: Poly (vinyl alcohol) (PVA)/ multi-layered graphene (MLG) / multi-walled carbon nanotubes (MWCNT) nanocomposites of different compositions were made through the solution casting method. Filler loadings used were 20 wt. % MLG, 17.5 wt.% MLG / 2.5 wt.% MLG, 15 wt.% MLG / 5 wt.% MWCNT and 10 wt.% MLG / 10 wt.% MWCNT. Mechanical strength of the composites was evaluated by testing their tensile and viscoelastic properties. Differential thermal analysis (DTA) showed improved thermal stability for hybrid composites when compared to that of PVA/ 20 wt.% MLG composite. A 2 mm hot pressed multilayered structure of hybrid composite (10 wt.% MLG / 10 wt.% MWCNT) exhibited the EMI shielding effectiveness of ∼ 39 dB in the X-band. The electrical conductivity of the hybrid composites improved significantly with MWCNT content and reached to the order of 10 -5 S/cm with a 10 wt.% MWCNT addition. The hybrid composites also exhibited superior wear resistance when compared with that of PVA/ MLG composite of same filler loading.